3D antennas for wireless power transmission - Dias, Gonçalo Amorim (2017)
The 3D printing has seen a very strong growth in the last ﬁve years, especially since began to appear solutions of this kind of technology at much lower prices and for common user. The design of freedom associated with the three-dimensional structures can create complex geometries that produce very speciﬁc characteristics of radiation for very demanding applications. Today, it is possible to do this without big budgets. In this dissertation the lens based solution is explored through 3D printing technology. Three antennas are presented, one microstrip coupled antenna without lens, the second with an extended hemispherical lens and the third with a spherical lens. The purpose of these antennas is to provide or capture power for passive sensor networks in space. These antennas operate in the K band, more speciﬁcally at 20 GHz. In these frequencies, the lenses become acceptable in size for many applications. With this dissertation it was concluded that the use of printed lenses in 3D printers is an interesting solution to increase the gain and to focus the electromagnetic ﬁeld of an antenna. These characteristics allow to create small and compact antennas with a high gain that can perform a similar performance to others with higher cost and dimensions, such as reﬂectors, arrays, or horn antennas.